Novel Selective and Low-Toxic Inhibitor of LmCPB2.8ΔCTE (CPB) One Important Cysteine Protease for Leishmania Virulence - Moreira, Vitor Partite [UNESP]; da Silva Mela, Michele Ferreira [UNESP]; Anjos, Luana Ribeiro dos [UNESP]; Saraiva, Leonardo Figueiredo [UNESP]; Arenas Velásquez, Angela M. [UNESP]; Kalaba, Predrag; Fabisiková, Anna; Clementino, Leandro da Costa [UNESP]; Aufy, Mohammed; Studenik, Christian; Gajic, Natalie; Prado-Roller, Alexander; et al. (MDPI, 2022)
Leishmaniasis is a highly prevalent, yet neglected disease caused by protozoan parasites of the genus Leishmania. In the search for newer, safer, and more effective antileishmanial compounds, we herein present a study of the mode of action in addition to a detailed structural and biological characterization of LQOF-G6 [N-benzoyl-N′-benzyl-N″-(4-tertbutylphenyl)guanidine]. X-ray crystallography and extensive NMR experiments revealed that LQOF-G6 nearly exclusively adopts the Z conformation stabilized by an intramolecular hydrogen bond. The investigated guanidine showed selective inhibitory activity on Leishmania major cysteine protease LmCPB2.8ΔCTE (CPB) with ~73% inhibition and an IC50-CPB of 6.0 µM. This compound did not show any activity against the mammalian homologues cathepsin L and B. LQOF-G6 has been found to be nontoxic toward both organs and several cell lines, and no signs of hepatotoxicity or nephrotoxicity were observed from the analysis of biochemical clinical plasma markers in the treated mice. Docking simulations and experimental NMR measurements showed a clear contribution of the conformational parameters to the strength of the binding in the active site of the enzyme, and thus fit the differences in the inhibition values of LQOF-G6 compared to the other guanidines. Furthermore, the resulting data render LQOF-G6 suitable for further development as an antileishmanial drug.
Keywords: guanidines; Leishmania cysteine protease inhibition; leishmanicidal activity; molecular docking; X-ray and NMR conformational study